Long-Term Visuo-Gustatory Appetitive and Aversive Conditioning Potentiate Human Visual Evoked Potentials - Christoffersen, Gert R. J.; Laugesen, Jakob L.; Møller, Per; Bredie, Wender L. P.; Schachtman, Todd R.; Liljendahl, Christina; Viemose, Ida (Frontiers in Human Neuroscience, 2017)
Human recognition of foods and beverages are often based on visual cues associated with flavors. The dynamics of neurophysiological plasticity related to acquisition of such long-term associations has only recently become the target of investigation. In the present work, the effects of appetitive and aversive visuo-gustatory conditioning were studied with high density EEG-recordings focusing on late components in the visual evoked potentials (VEPs), specifically the N2-P3 waves. Unfamiliar images were paired with either a pleasant or an unpleasant juice and VEPs evoked by the images were compared before and one day after the pairings. In electrodes located over posterior visual cortex areas, the following changes were observed after conditioning: The amplitude from the N2-peak to the P3-peak increased and the N2 peak delay was reduced. The percentage increase of N2-to-P3 amplitudes was asymmetrically distributed over the posterior hemispheres despite the fact that the images were bilaterally symmetrical across the two visual hemifields. The percentage increases of N2-to-P3 amplitudes in each experimental subject correlated with the subject’s evaluation of positive or negative hedonic valences of the two juices. Results from 118 scalp electrodes gave surface maps of theta power distributions showing increased power over posterior visual areas after the pairings. Source current distributions calculated from swLORETA revealed that visual evoked currents rose as a result of conditioning in five cortical regions - from primary visual areas and into the inferior temporal gyrus. These learning-induced changes were seen after both appetitive and aversive training while a sham trained control group showed no changes. It is concluded that long-term visuo-gustatory conditioning potentiated the N2-P3 complex, and it is suggested that the changes are regulated by the perceived hedonic valence of the US.